Understanding Cultural Persistence and Change: A Replication of Giuliano and Nunn (2021) - Simone Bertoli; Melchior Clerc; Jordan Loper; Èric Roca Fernández (Institute for Replication (I4R), 2024)
Giuliano and Nunn (2021), GN henceforth, provide econometric evidence that ancestral climatic variability is negatively associated with the current importance of tradition using a variety of data sources. This replication focuses on the results that use individual-level data and identifies major discrepancies between several econometric specifications described in the article and their corresponding code. We are able to correct most of these mistakes by realigning the code with the text. Once corrections are implemented, we obtain almost invariably a smaller and non-significant coefficient for climatic variability.
Keywords: F22; Z13; N10; Q54; 330; cultural persistence; tradition; languages